Mechanisms of Resistance to Hsp90 Inhibitor Drugs: A Complex Mosaic Emerges - Peter W. Piper (Pharmaceuticals, 2011)
The molecular chaperone Hsp90 holds great promise as a cancer drug target, despite some of the initial clinical trials of Hsp90 inhibitor drugs having not lived up to expectation. Effective use of these drugs will benefit greatly from a much more detailed understanding of the factors that contribute to resistance, whether intrinsic or acquired. We review how cell culture studies have revealed a number of different mechanisms whereby cells can be rendered less susceptible to the effects of Hsp90 inhibitor treatment. A major influence is Hsp90 inhibition causing strong induction of the heat shock response, a stress response that increases cellular levels of prosurvival chaperones such as Hsp27 and Hsp70. Another problem seems to be that these inhibitors do not always access the Hsp90 proteins of the mitochondrion, forms of Hsp90 that—in cancer cells—are operating to suppress apoptosis. It should be possible to overcome these drawbacks through the appropriate drug redesign or with the combinatorial use of an Hsp90 inhibitor with a drug that targets either heat shock factor or the chaperone Hsp70. Still though, cells will often differ in the key antiapoptotic versus proapoptotic activities that are dependent on Hsp90, in the key steps in their apoptotic pathways responsive to Hsp90 inhibition or Hsp70 level, as well as the extents to which their survival is dependent on oncogenic tyrosine kinases that are clients of Hsp90. A systems approach will therefore often be required in order to establish the most prominent effects of Hsp90 inhibition in each type of cancer cell.